In search of a ‘developmental state’ - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2024)
This Special Issue on Economics and Labour is divided into two sections. It pairs contributions on current economic development with three articles presented at a conference marking 50 years since the Durban Strikes of 1973. That said, all of the authors reflect widely on history and on immediate challenges, both for South Africa and the continent at large.